Higher investment levels into pre-planned routes increase the adherence of pedestrians to them. (October 2021) - Tong, Yunhe; Bode, Nikolai W.F.
Highlights: Pedestrians are more likely to stick to pre-planned routes as their investment into them increases. We term this behaviour "route commitment effect" and formalise it in a route choice model. The route commitment effect can reduce the efficiency of pedestrian flow. It can also make pedestrian dynamics more predictable. Abstract: Extensive research has focused on identifying the principles in pedestrian route choice, often assuming that pedestrians follow an optimal route measured by factors, such as route length and busyness. However, the question of the extent to which pedestrians adhere to their planned route has not been convincingly resolved. Here, we form the hypothesis that the more pedestrians invest into a planned route by walking further along it, the bigger their tendency to stick to this route, even when it becomes less attractive than other options due to congestion, for example. We term this behaviour "route commitment effect" and conduct an online survey with over 300 participants to test and establish the existence of this effect. We propose a novel model to formalise this effect. Using simulations of our model, we give illustrative examples for the consequences of the route commitment effect. Our findings suggest that the route commitment effect can significantly influence pedestrian route choice in a simple scenario with only two possible routes. In more complex scenarios with many routes, the impact of the route commitment effect on the overall dynamics is much weaker, as pedestrians are distributed across routes. In general, we find that the route commitment effect reduces the efficiency of pedestrian flow and leads to more predictable pedestrian dynamics. Our study sheds light on the role of cognitive bias in pedestrian decision-making and may thus be helpful for facility design or operations.